Fast self-curing α-tricalcium phosphate/β-dicalcium silicate composites beneficial for root canal sealing treatment - Youyang Zheng; Xianyan Yang; Shuxin Liu; Siqi Bao; Yuyue Xu; Yunyi Wang; Feng Zhang; Zhongru Gou (Heliyon, 2022)
Objectives: α-tricalcium phosphate (α-TCP) and β-dicalcium silicate (β-C2S) have attracted much attention since these two types of self-curing Ca-phosphate and Ca-silicate are valuable biomaterials for bone defect or endodontic therapy. However, the injectable paste of their individual with high liquid/solid ratio is junior for root canal sealing due to very long self-setting time, low pH value and/or much volume shrinkage during paste-to-cement transformation. Methods: Our studies evaluated the effect of biphasic ratio, liquid/solid ratio and pH condition of aqueous medium on setting time and mechanical strength of this biphasic composite cement, and also the hydroxyapatite re-mineralization potential and anti-microleakage level of the cements with different α-TCP/β-C2S ratio were explored in vitro. A control group free of paste filler was included in the extracted teeth model. Dentine re-mineralization and microleakage degree were observed by scanning electron microscopy and microCT reconstruction analysis. Results: It indicated that the weak acidic solution with pH value of 6.0 may produce a significantly shorter initial setting time (from 90 min to less 20 min) and expected final setting time (<150 min) for the biphasic composite (2:1 or 1:2) in comparison with the pure β-C2S. Notably, the phasic composites exhibited limited microleakage and induced hydroxyapatite mineralization in the dentine tubules. These hydraulic pastes also produced strong alkaline feature and appreciable compressive resistance (12–18 MPa) after setting for a very short time stage. Moreover, a link between the addition of α-TCP leading to fast re-mineralization reaction was established. Significance: Our findings suggest that the appreciable self-setting and physicochemical properties adaption to root canal sealability make α-TCP/β-C2S composites as preferential candidates for endodontic treatments.